2003
DOI: 10.1177/039139880302601006
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Loss across the Hemofilter during Continuous Hemofiltration

Abstract: Background Thrombocytopenia is a common finding in patients in the intensive care unit receiving continuous renal replacement therapy (CRRT). It is unknown if the hemofilter itself contributes to the platelet loss. Objective To measure the direct effect of the hemofilter on platelet counts during CRRT. Design Prospective, observational study Setting Intensive care unit of a University hospital Patients Critically ill patients with acute renal failure receiving CRRT. Methods Two samples of blood were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 11 publications
2
34
0
1
Order By: Relevance
“…Recently, Mulder et al [3] have reported that hemofiltration itself is one of the important reasons in thrombocytopenia during CVVH. However, there are no reports on whether differ- ent hemofilters affect platelet counts differently during CVVH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Mulder et al [3] have reported that hemofiltration itself is one of the important reasons in thrombocytopenia during CVVH. However, there are no reports on whether differ- ent hemofilters affect platelet counts differently during CVVH.…”
Section: Discussionmentioning
confidence: 99%
“…However, the hemofilter itself plays an important role in the genesis of thrombocytopenia as a result of immediate destruction or retention of platelets as they pass through the filter [3] . Thrombogenicity of a dialysis membrane depends on the composition of the membrane as well as on the area and geometry of the dialyzer.…”
mentioning
confidence: 99%
“…The authors estimated a total daily platelet loss of 625 Â 10 9 cells, displaying the demand placed on platelet production to maintain counts. 12 The filter type has also been implicated in platelet loss, suggesting a more substantial decline depending on hemofilter type. Liu et al compared platelet loss across a polysulfone and cellulose triacetate filters with or without anticoagulation.…”
Section: Platelet Statisticsmentioning
confidence: 99%
“…While the literature is minimal, this data signifies not only the presence of a reduction in platelets in patients on CRRT, but the relation of specific CRRT attributes to the risk and degree of platelet loss. 1,10,12 Missing from this literature is the pathology in which thrombocytopenia develops. Oever et al suggested a trapping phenomenon in the extracorporeal circuit resulting in activation of the platelets and sequestration.…”
Section: Platelet Statisticsmentioning
confidence: 99%
See 1 more Smart Citation